Long bone scaling in Captorhinidae: do limb bones scale according to elastic similarity in sprawling basal amniotes?. (29th January 2019) - Romano, Marco; Rubidge, Bruce
Abstract : Captorhinids are a speciose clade of sauropsids that are crucial to understand several aspects of basal amniote general biology. Members of the Captorhinidae explored different diets and, amongst basal amniotes, were one of the first groups to demonstrate high‐fibre herbivory. Several papers have been published on the cranial anatomy of captorhinids, but there are relatively few studies which focus on the post‐cranium, especially on the appendicular skeleton and long bones. This contribution presents the first quantitative long bone scaling in Captorhinidae performed through morphometric analyses. From classical biomechanical research, it is well‐established that to accommodate an increase in size, gravity will result in elastic deformation of long bones. This outcome is especially significant in terrestrial tetrapods with a sprawling limb posture such as captorhinids, where great torsional stresses are applied to long bones, both during locomotion and in the resting phase. In this paper, we test whether the consistent evolutionary size increase in captorhinids led to major re‐patterning in long bone structure as theoretically expected, based on the theory of elastic similarity. Morphometric analysis shows that, apart from a small positive allometry in the humerus, captorhinid long bones scale geometrically as body size increases. Thus, the predicted elastic similarity to maintain similar levels in peak stress with an increase in dimensions does not seem not to apply to long bone evolution in captorhinids. We propose that, as already observed experimentally in larger‐bodied varanid lizards, large captorhinids could also mitigate size‐related increases in stress by reducing femur rotation and increasing the percentage of the stride cycle during which the right hindfoot was on the ground (i.e. the duty factor). In this way, large captorhinids could avoid reaching peak stress thresholds by sacrificing speed during locomotion and without a substantial long bone re‐patterning or postural change.